DECISION SUPPORT SYSTEM FOR RESIDENTIAL LAND SELECTION USING SMART METHOD: SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE - Azzahro, Erina; Supriyono, Supriyono; Setiaji, Pratomo (JATI (Jurnal Mahasiswa Teknik Informatika), 2025)
PT. Abra, a property development company specializing in residential housing, faces challenges in selecting strategic land for its projects, often leading to inefficiencies in decision-making. The main issue is the lack of an integrated system to assess multiple criteria, such as location, price, accessibility, and infrastructure availability. To overcome this, a Decision Support System (DSS) is developed using the Simple Multi-Attribute Rating Technique (SMART) method, enabling systematic evaluation based on predefined criteria. The system follows the Rapid Application Development (RAD) methodology, which consists of requirements planning, user design, construction, and cutover phases, ensuring flexibility and efficiency. A MySQL database is used for structured data management, while Blackbox testing is conducted to validate system functionality, ensuring accuracy and reliability. The results show that the DSS improves decision-making efficiency, reduces selection errors, and optimizes land acquisition for residential projects. Furthermore, it enhances transparency in land selection by providing real-time data analysis and ranking of potential locations. This research contributes to the real estate sector by improving strategic planning, resource allocation, and overall project success, providing a structured and effective approach to optimizing land selection processes.